A refractory and wear-resistant castable combined with ultrafine powder and preparation method thereof
By combining the ratio and preparation method of ultrafine powder in the refractory castable, the problem of poor wear resistance of existing refractory castables is solved, and higher wear resistance and corrosion resistance are achieved, and service life is extended.
Patent Information
- Application Number
- CN202411878208.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
AI Technical Summary
The wear resistance of existing refractory castables is poor and are prone to wear and peeling caused by powder erosion in environments with high dust, affecting their service life.
Refractory and wear-resistant castables combined with ultrafine powder, including corundum powder, silicon powder, silicon carbide powder, bauxite clinker, zircon, tungsten carbide/aluminum nitride composite particles and sulfurite pulp waste liquid, are used as bonding agents, and the density, strength and wear resistance of the castables are improved through reasonable proportioning and preparation methods.
It significantly improves the wear resistance and corrosion resistance of refractory castables, extends service life, and ensures refractory performance and density.
Smart Images

Figure BDA0005197483380000081 
Figure BDA0005197483380000091 
Figure BDA0005197483380000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a refractory and wear-resistant casting material combined with ultrafine powder and a preparation method thereof. Background Art
[0002] Castable is a granular and powdered material made of refractory substances. It is an amorphous refractory material with high fluidity, constructed by pouring method, and can be hardened without heating. It is generally formed at the site of use by pouring, vibration or tamping, and can also be made into prefabricated parts for use.
[0003] Refractory castables are the most widely produced and used amorphous refractory materials, mainly used to construct various heating furnace linings and other integral structures, and some high-quality varieties can also be used in smelting furnaces. Existing refractory castables have poor wear resistance and will be eroded by powder for a long time in a dusty environment, causing the refractory castables to wear and peel off, which affects the service life of the refractory. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a refractory and wear-resistant castable combined with ultrafine powder and a preparation method thereof.
[0005] The technical solution of the present invention is: a refractory and wear-resistant castable combined with ultrafine powder, which comprises the following components by weight: 50-60 parts of corundum powder, 10-15 parts of silicon powder, 4-8 parts of silicon carbide powder, 15-25 parts of bauxite clinker, 6-9 parts of zircon, 10-15 parts of tungsten carbide / aluminum nitride composite particles, and 5-7 parts of a binder.
[0006] Description: The above castables are made of corundum powder combined with other raw materials, so that the castables can obtain higher density and strength after solidification, and ensure the refractory and corrosion resistance of the refractory. The tungsten carbide / aluminum nitride composite particles can be well combined with the castable structure and dispersed in the castable to improve the wear resistance and corrosion resistance of the castable.
[0007] Furthermore, the corundum powder comprises, by weight: 10 to 14 parts of corundum fine powder with a particle size of 1 to 5 μm, 18 to 21 parts of corundum medium powder with a particle size of 75 to 120 μm, and 22 to 25 parts of corundum coarse powder with a particle size of 1 to 3 mm.
[0008] Note: The ratio of the corundum powder with the above particle size is reasonable. The fine corundum powder can fully fill the gap between the medium corundum powder and the coarse corundum powder to ensure the structural density of the castable.
[0009] Furthermore, the binder is sulfite pulp waste liquid.
[0010] Description: The above-mentioned binder has low use cost and can effectively combine the castable particles to ensure the strength of the castable.
[0011] Furthermore, the preparation method of tungsten carbide / aluminum nitride composite particles comprises the following steps:
[0012] S1. Dissolve aluminum chloride in deionized water and stir until completely dissolved to obtain an aluminum chloride solution; wherein the mass ratio of aluminum chloride to deionized water is 1:6-7;
[0013] S2, adding tungsten carbide powder into anhydrous ethanol, then adding polyacrylic acid into the anhydrous ethanol, and ultrasonically dispersing for 15 to 30 minutes to obtain a tungsten carbide powder dispersion; wherein the mass ratio of tungsten carbide powder, anhydrous ethanol and polyacrylic acid is 1:4 to 5:0.3 to 0.5;
[0014] S3, heating the aluminum chloride solution to 60-70°C, and then continuously adding 10-20°C tungsten carbide powder dispersion to the aluminum chloride solution under stirring, the amount of tungsten carbide powder dispersion added per minute accounting for 3-6% of the initial mass of the aluminum chloride solution; when the temperature of the aluminum chloride solution drops to 45-55°C, stop adding the tungsten carbide powder dispersion, and add sodium hydroxide solution to the aluminum chloride solution once, the single addition amount of sodium hydroxide solution accounting for 1-2% of the initial mass of the aluminum chloride solution; irradiate the aluminum chloride solution with ultraviolet light during the heating process of the aluminum chloride solution;
[0015] S4, repeat step S3 until the mass ratio of the added tungsten carbide powder dispersion to the aluminum chloride solution reaches 1-1.25:1, continue stirring for 3-4 hours and then filter to obtain tungsten carbide loaded with aluminum hydroxide gel;
[0016] S5. Place the tungsten carbide loaded with aluminum hydroxide gel into a sintering furnace and keep it at 500-600°C for 4-6 hours. After the heat preservation is completed, evacuate the sintering furnace to a vacuum of 1-3×10 -1 Pa, and then nitrogen is filled into the sintering furnace and the temperature of the sintering furnace is increased to 1600-1700°C, and the temperature is kept again for 10-12 hours. After the second heat preservation is completed, tungsten carbide / aluminum nitride composite particles are obtained.
[0017] Description: The above method loads aluminum hydroxide gel on tungsten carbide powder, converts aluminum hydroxide gel into aluminum oxide at high temperature, and generates aluminum nitride on the tungsten carbide powder in situ by the reaction of nitrogen and aluminum oxide, so that a diffusion bonding layer is formed between the aluminum nitride interface and the tungsten carbide interface, so that the tungsten carbide / aluminum nitride composite particles are well bonded with the castable structure, avoiding the agglomeration of tungsten carbide particles in the castable structure, resulting in increased brittleness of the castable.
[0018] Furthermore, in step S3, the mass concentration of the sodium hydroxide solution is 10-15%.
[0019] Note: The sodium hydroxide solution of the above concentration can ensure the reaction rate, make aluminum chloride react fully, and is easy to prepare and safe to use.
[0020] Furthermore, in step S3, the irradiation power of the ultraviolet light is 800-1200W, and the irradiation distance is 5-10cm.
[0021] Note: Ultraviolet irradiation can promote the cross-linking of polyacrylic acid, so that the tungsten carbide powder can fully load the aluminum hydroxide gel.
[0022] Furthermore, in step S5, during the nitrogen filling process, the pressure increasing rate of the sintering furnace is 0.2-0.4 MPa / h, and the temperature increasing rate is 5-8°C / min.
[0023] Note: Limiting the pressure increase rate and the temperature increase rate can ensure that the aluminum oxide fully reacts with the nitrogen, so that the aluminum oxide is fully converted into aluminum nitride, and a diffusion bonding layer is formed between the tungsten carbide interface and the aluminum nitride interface.
[0024] On the other hand, the present invention provides a method for preparing a refractory and wear-resistant castable combined with ultrafine powder, which is used to prepare the above-mentioned castable, comprising the following steps:
[0025] 1) adding corundum powder, silicon powder, silicon carbide powder, bauxite clinker, zircon, and tungsten carbide / aluminum nitride composite particles into a mixer according to the weight portions, and stirring for 10 to 20 minutes to obtain a mixture;
[0026] 2) Divide the binder into 2 to 4 equal parts, heat the mixture while stirring, and heat the mixture at a rate of 3 to 5°C / min. For every 8 to 10°C increase in the temperature of the mixture, add one part of the binder to the mixture until all the binder is added to the mixture. Stop heating and continue stirring for 5 to 10 minutes to obtain a castable.
[0027] Note: The above preparation method adds the binder in batches so that the binder can be evenly dispersed in the mixture, thereby ensuring the bonding strength between the mixture particles and the structural density of the castable, so that the castable has good strength and wear resistance.
[0028] The beneficial effects of the present invention are:
[0029] (1) The present invention combines corundum powder with other raw materials to obtain a higher density and strength of the castable after solidification, and ensures the refractory and corrosion resistance of the refractory. The tungsten carbide / aluminum nitride composite particles can be well combined with the castable structure and dispersed in the castable to improve the wear resistance and corrosion resistance of the castable.
[0030] (2) The present invention loads aluminum hydroxide gel on tungsten carbide powder, converts the aluminum hydroxide gel into aluminum oxide at high temperature, and generates aluminum nitride on the tungsten carbide powder in situ by reacting nitrogen with aluminum oxide, so that a diffusion bonding layer is formed between the aluminum nitride interface and the tungsten carbide interface, so that the tungsten carbide / aluminum nitride composite particles are well bonded with the castable structure, thereby preventing the tungsten carbide particles from agglomerating in the castable structure and causing the castable to become more brittle.
[0031] (3) The preparation method of the present invention adds the binder in batches so that the binder can be evenly dispersed in the mixture, thereby ensuring the bonding strength between the particles of the mixture and the structural density of the castable, so that the castable has good strength and wear resistance. DETAILED DESCRIPTION
[0032] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0033] Embodiment 1: A refractory and wear-resistant castable combined with ultrafine powder, comprising the following components by weight: 55 parts of corundum powder, 12 parts of silicon powder, 6 parts of silicon carbide powder, 20 parts of bauxite clinker, 8 parts of zircon, 12 parts of tungsten carbide / aluminum nitride composite particles, and 6 parts of a binder; by weight, the corundum powder comprises: 12 parts of corundum fine powder with a particle size of 1 to 5 μm, 20 parts of corundum medium powder with a particle size of 75 to 120 μm, and 24 parts of corundum coarse powder with a particle size of 1 to 3 mm; the binder is sulfite pulp waste liquid;
[0034] The preparation method of tungsten carbide / aluminum nitride composite particles comprises the following steps:
[0035] S1. Dissolve aluminum chloride in deionized water and stir until completely dissolved to obtain an aluminum chloride solution; wherein the mass ratio of aluminum chloride to deionized water is 1:6.5;
[0036] S2, adding tungsten carbide powder into anhydrous ethanol, then adding polyacrylic acid into the anhydrous ethanol, and ultrasonically dispersing for 23 minutes to obtain a tungsten carbide powder dispersion; wherein the mass ratio of tungsten carbide powder, anhydrous ethanol and polyacrylic acid is 1:4.5:0.4; and the particle size of the tungsten carbide powder is 1-4 μm;
[0037] S3, heating the aluminum chloride solution to 65°C, and then continuously adding 15°C tungsten carbide powder dispersion to the aluminum chloride solution under stirring, the amount of tungsten carbide powder dispersion added per minute accounting for 5% of the initial mass of the aluminum chloride solution; when the temperature of the aluminum chloride solution drops to 50°C, stop adding the tungsten carbide powder dispersion, and add a sodium hydroxide solution with a mass concentration of 12% to the aluminum chloride solution once, and the single addition amount of the sodium hydroxide solution accounts for 1.5% of the initial mass of the aluminum chloride solution; during the heating process of the aluminum chloride solution, the aluminum chloride solution is irradiated with ultraviolet light, wherein the irradiation power of the ultraviolet light is 1000W and the irradiation distance is 8cm;
[0038] S4, repeat step S3 until the mass ratio of the added tungsten carbide powder dispersion to the aluminum chloride solution reaches 1:1.15, continue stirring for 3.5 hours and then filter to obtain tungsten carbide loaded with aluminum hydroxide gel;
[0039] S5. Put the tungsten carbide loaded with aluminum hydroxide gel into a sintering furnace and keep it at 550°C for 5 hours. After the heat preservation is completed, evacuate the sintering furnace to 2×10 -1 Pa, then nitrogen is charged into the sintering furnace and the temperature of the sintering furnace is increased to 1650°C, and the temperature is kept for 11 hours again. After the heat preservation is completed again, tungsten carbide / aluminum nitride composite particles are obtained; during the process of charging nitrogen, the pressure increase rate of the sintering furnace is 0.3MPa / h, and the temperature increase rate is 7°C / min;
[0040] On the other hand, the method for preparing the above castable comprises the following steps:
[0041] 1) adding corundum powder, silicon powder, silicon carbide powder, bauxite clinker, zircon, and tungsten carbide / aluminum nitride composite particles into a mixer according to weight, and stirring for 15 minutes to obtain a mixture;
[0042] 2) Divide the binder into 3 equal parts, heat the mixture while stirring, and heat the mixture at a heating rate of 4°C / min. For every 9°C increase in the temperature of the mixture, add one part of the binder to the mixture until all the binder is added to the mixture. Stop heating and continue stirring for 8 minutes to obtain the castable.
[0043] Example 2: This example is basically the same as Example 1, except that the castable includes the following ingredients by weight: 50 parts of corundum powder, 10 parts of silicon micropowder, 4 parts of silicon carbide powder, 15 parts of bauxite clinker, 6 parts of zircon, 10 parts of tungsten carbide / aluminum nitride composite particles, and 5 parts of binder.
[0044] Example 3: This example is basically the same as Example 1, except that the castable includes the following components by weight: 60 parts of corundum powder, 15 parts of silicon micropowder, 8 parts of silicon carbide powder, 25 parts of bauxite clinker, 9 parts of zircon, 15 parts of tungsten carbide / aluminum nitride composite particles, and 7 parts of binder.
[0045] Example 4: This example is basically the same as Example 1, except that, by weight, the corundum powder includes: 10 parts of corundum fine powder with a particle size of 1 to 5 μm, 18 parts of corundum medium powder with a particle size of 75 to 120 μm, and 22 parts of corundum coarse powder with a particle size of 1 to 3 mm.
[0046] Example 5: This example is basically the same as Example 1, except that, by weight, the corundum powder includes: 14 parts of corundum fine powder with a particle size of 1 to 5 μm, 21 parts of corundum medium powder with a particle size of 75 to 120 μm, and 25 parts of corundum coarse powder with a particle size of 1 to 3 mm.
[0047] Example 6: This example is basically the same as Example 1, except that when the temperature of the aluminum chloride solution drops to 45°C, the addition of the tungsten carbide powder dispersion is stopped.
[0048] Example 7: This example is basically the same as Example 1, except that when the temperature of the aluminum chloride solution drops to 55°C, the addition of the tungsten carbide powder dispersion is stopped.
[0049] Example 8: This example is basically the same as Example 1, except that the mass ratio of the added tungsten carbide powder dispersion to the aluminum chloride solution reaches 1:1.
[0050] Example 9: This example is basically the same as Example 1, except that the mass ratio of the added tungsten carbide powder dispersion to the aluminum chloride solution reaches 1:1.25.
[0051] Example 10: This example is basically the same as Example 1, except that the amount of tungsten carbide powder dispersion added per minute accounts for 3% of the initial mass of the aluminum chloride solution.
[0052] Example 11: This example is basically the same as Example 1, except that the amount of tungsten carbide powder dispersion added per minute accounts for 6% of the initial mass of the aluminum chloride solution.
[0053] Example 12: This example is substantially the same as Example 1, except that the single addition amount of the sodium hydroxide solution accounts for 1% of the initial mass of the aluminum chloride solution.
[0054] Example 13: This example is basically the same as Example 1, except that the single addition amount of the sodium hydroxide solution accounts for 2% of the initial mass of the aluminum chloride solution.
[0055] Example 14: This example is basically the same as Example 1, except that the irradiation power of the ultraviolet light is 800W.
[0056] Example 15: This example is basically the same as Example 1, except that the irradiation power of the ultraviolet light is 1200W.
[0057] Example 16: This example is basically the same as Example 1, except that the tungsten carbide loaded with aluminum hydroxide gel is placed in a sintering furnace and kept at 500°C for 5 hours. After the heat preservation is completed, the sintering furnace is evacuated to 2×10 -1 Pa, then nitrogen was filled into the sintering furnace and the temperature of the sintering furnace was increased to 1600°C, and then kept warm for 11 hours.
[0058] Example 17: This example is basically the same as Example 1, except that the tungsten carbide loaded with aluminum hydroxide gel is placed in a sintering furnace and kept at 600°C for 5 hours. After the heat preservation is completed, the sintering furnace is evacuated to 2×10 -1 Pa, then nitrogen was filled into the sintering furnace and the temperature of the sintering furnace was increased to 1700°C, and then kept warm for 11 hours.
[0059] Example 18: This example is basically the same as Example 1, except that the binder is divided into two equal parts.
[0060] Example 19: This example is basically the same as Example 1, except that the binder is divided into 4 equal parts.
[0061] Comparative Example 1: Using Example 1 as a reference, the tungsten carbide / aluminum nitride composite particles were replaced with tungsten carbide powder.
[0062] Comparative Example 2: Taking Example 1 as a reference, the tungsten carbide / aluminum nitride composite particles were replaced with aluminum nitride powder.
[0063] Comparative Example 3: Taking Example 1 as a reference, the tungsten carbide powder dispersion and the sodium hydroxide solution were added into the aluminum chloride solution at one time.
[0064] Comparative Example 4: Using Example 1 as a reference, the aluminum chloride solution was not irradiated with ultraviolet light during the heating process.
[0065] Comparative Example 5: Taking Example 1 as a reference, the binder was added into the mixture at one time.
[0066] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the castable, the castable of each embodiment was sampled, cured and baked, and then the post-firing linear change rate of the sample of each embodiment was tested under the condition of 1100℃×3h, and the sample of each embodiment was subjected to room temperature erosion and wear test, and the wear time was 2h. After the experiment was completed, the mass loss rate before and after wear was calculated, and the specific exploration was as follows:
[0067] Experimental Example 1: Investigating the influence of castable composition on performance
[0068] Using Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2 as experimental comparisons, the castable properties under different compositions are shown in Table 1 below:
[0069] Table 1 Castable properties under different compositions
[0070] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.093 0.15 Example 2 0.108 0.19 Example 3 0.115 0.23 Example 4 0.098 0.18 Example 5 0.102 0.21 Comparative Example 1 0.260 0.35 Comparative Example 2 0.207 0.44
[0071] It can be seen from the data in Table 1 that, compared with Examples 1, 2, and 3, the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because the castable of Example 1 has the least internal defects, so the castable selected in Example 1 has the best performance.
[0072] Compared with Examples 1, 4, and 5: the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance, which may be because the castable structure is the densest under the corundum powder ratio selected in Example 1;
[0073] Example 1 is compared with Comparative Examples 1 and 2: After the tungsten carbide / aluminum nitride composite particles are replaced with tungsten carbide powder or aluminum nitride granular powder, the thermal stability and wear resistance of the castable are reduced. This may be because the pure tungsten carbide powder cannot be evenly dissolved into the castable structure, resulting in the tungsten carbide particles being unable to fully strengthen the castable.
[0074] Experimental Example 2: Investigating the effect of the temperature of the loaded aluminum chloride solution on the performance of the castable
[0075] Using Examples 1, 6, and 7 as experimental comparisons, the castable properties of the aluminum chloride solution at different temperatures are shown in Table 2 below:
[0076] Table 2 Castable properties of aluminum chloride solution at different temperatures
[0077] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.083 0.15 Example 6 0.094 0.22 Example 7 0.096 0.20
[0078] It can be seen from the data in Table 2 that the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because at the temperature of the aluminum chloride solution in Example 1, aluminum chloride and sodium hydroxide can fully react, so the temperature of the aluminum chloride solution selected in Example 1 is optimal.
[0079] Experimental Example 3: Investigating the effect of the ratio of aluminum chloride solution to tungsten carbide powder dispersion on castable properties
[0080] Using Examples 1, 8, and 9 as experimental comparisons, the castable properties of the aluminum chloride solution and the tungsten carbide powder dispersion at different ratios are shown in Table 3 below:
[0081] Table 3 Castable properties at different ratios of aluminum chloride solution and tungsten carbide powder dispersion
[0082] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.083 0.15 Example 8 0.104 0.21 Example 9 0.098 0.19
[0083] It can be seen from the data in Table 3 that the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because under the tungsten carbide powder dispersion ratio selected in Example 1, the tungsten carbide powder can fully load the aluminum hydroxide gel, so the ratio of aluminum chloride solution to tungsten carbide powder dispersion selected in Example 1 is optimal.
[0084] Experimental Example 4: Investigating the effect of tungsten carbide powder dispersion addition rate on castable properties
[0085] Using Examples 1, 10, 11 and Comparative Example 3 as experimental comparisons, the castable properties of the tungsten carbide powder dispersion at different addition rates are shown in Table 4 below:
[0086] Table 4 Castable properties of tungsten carbide powder dispersion at different addition rates
[0087] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.083 0.15 Example 10 0.099 0.20 Embodiment 11 0.094 0.18 Comparative Example 3 0.195 0.31
[0088] It can be seen from the data in Table 4 that the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because the conversion rate of tungsten carbide / aluminum nitride composite particles is the highest at the addition rate of the tungsten carbide powder dispersion selected in Example 1, so the addition rate of the tungsten carbide powder dispersion selected in Example 1 is optimal.
[0089] Experimental Example 5: Investigating the effect of sodium hydroxide solution addition on castable properties
[0090] Using Examples 1, 12, and 13 as experimental comparisons, the castable properties obtained under different addition amounts of sodium hydroxide solution are shown in Table 5 below:
[0091] Table 5 Castable properties under different addition amounts of sodium hydroxide solution
[0092] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.083 0.15 Example 12 0.089 0.18 Embodiment 13 0.087 0.17
[0093] It can be seen from the data in Table 5 that the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because aluminum chloride can fully participate in the reaction under the amount of sodium hydroxide solution added in Example 1, so the amount of sodium hydroxide solution added in Example 1 is optimal.
[0094] Experimental Example 6: Investigating the effect of UV irradiation power on castable properties
[0095] Using Examples 1, 14, 15 and Comparative Example 4 as experimental comparisons, the castable properties under different UV irradiation powers are shown in Table 6 below:
[0096] Table 6 Castable properties under different UV irradiation powers
[0097]
[0098]
[0099] It can be seen from the data in Table 6 that, compared with Examples 1, 14 and 15: the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because the loading amount of aluminum hydroxide gel on tungsten carbide powder is the largest under the ultraviolet light irradiation power of Example 1, so the amount of sodium hydroxide solution added selected in Example 1 is optimal.
[0100] Compared with Comparative Example 4, Example 1 shows that after the aluminum chloride solution is not irradiated with ultraviolet light, the thermal stability and wear resistance of the castable are reduced. This may be because after the aluminum chloride solution is not irradiated with ultraviolet light, the bonding strength between the aluminum hydroxide gel and the tungsten carbide powder decreases, resulting in the inability of tungsten carbide to form a diffusion bonding layer with aluminum nitride.
[0101] Example 7: Investigating the effect of sintering temperature of tungsten carbide loaded with aluminum hydroxide gel on the properties of castables
[0102] Using Examples 1, 16 and 17 as experimental comparisons, the castable properties of tungsten carbide loaded with aluminum hydroxide gel at different sintering temperatures are shown in Table 7 below:
[0103] Table 7 Casting material properties of tungsten carbide loaded with aluminum hydroxide gel at different sintering temperatures
[0104] Group Line change rate after burning (±%) Mass loss rate (%) Example 1 0.083 0.15 Example 16 0.085 0.17 Embodiment 17 0.092 0.20
[0105] It can be seen from the data in Table 7 that, compared with Examples 1, 14 and 15: the castable of Example 1 has the smallest linear change rate after sintering and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because at the sintering temperature of tungsten carbide loaded with aluminum hydroxide gel selected in Example 1, aluminum hydroxide gel can be fully converted into aluminum nitride and tightly combined with tungsten carbide, so the sintering temperature of tungsten carbide loaded with aluminum hydroxide gel selected in Example 1 is optimal.
[0106] Example 8: Investigating the influence of castable preparation parameters on castable properties
[0107] Using Examples 1, 18, 19, 20, 21 and Comparative Example 5 as experimental comparisons, the castable properties under different castable preparation parameters are shown in Table 8 below:
[0108] Table 8 Castable properties under different casting preparation parameters
[0109]
[0110]
[0111] It can be seen from the data in Table 8 that, compared with Examples 1, 18, and 19: the castable of Example 1 has the smallest linear change rate after firing and the lowest mass loss rate, indicating that the castable selected in Example 1 has the best thermal stability and wear resistance. This may be because the structure of the castable is the most compact under the number of binder additions in Example 1, so the number of binder additions selected in Example 1 is the best.
[0112] Compared with Comparative Example 5, Example 1 shows that after the binder is added to the mixture at one time, the thermal stability and wear resistance of the castable are reduced. This may be because after the binder is added to the mixture at one time, the binder cannot be evenly mixed with the castable.
Claims
1. A refractory and wear-resistant castable combined with ultrafine powder, characterized in that: The invention comprises the following ingredients by weight: 50-60 parts of corundum powder, 10-15 parts of silicon micropowder, 4-8 parts of silicon carbide powder, 15-25 parts of bauxite clinker, 6-9 parts of zircon, 10-15 parts of tungsten carbide / aluminum nitride composite particles and 5-7 parts of a binder.
2. A refractory and wear-resistant castable combined with ultrafine powder according to claim 1, characterized in that: In terms of weight, the corundum powder includes: 10 to 14 parts of fine corundum powder with a particle size of 1 to 5 μm, 18 to 21 parts of medium corundum powder with a particle size of 75 to 120 μm, and 22 to 25 parts of coarse corundum powder with a particle size of 1 to 3 mm.
3. A refractory and wear-resistant castable combined with ultrafine powder according to claim 1, characterized in that: The binder is sulfite pulp waste liquid.
4. The refractory and wear-resistant castable combined with ultrafine powder according to claim 1, characterized in that: The preparation method of tungsten carbide / aluminum nitride composite particles comprises the following steps: S1. Dissolve aluminum chloride in deionized water and stir until completely dissolved to obtain an aluminum chloride solution; wherein the mass ratio of aluminum chloride to deionized water is 1:6-7; S2, adding tungsten carbide powder into anhydrous ethanol, then adding polyacrylic acid into the anhydrous ethanol, and ultrasonically dispersing for 15 to 30 minutes to obtain a tungsten carbide powder dispersion; wherein the mass ratio of tungsten carbide powder, anhydrous ethanol and polyacrylic acid is 1:4 to 5:0.3 to 0.5; S3, heating the aluminum chloride solution to 60-70°C, and then continuously adding 10-20°C tungsten carbide powder dispersion to the aluminum chloride solution under stirring, the amount of tungsten carbide powder dispersion added per minute accounting for 3-6% of the initial mass of the aluminum chloride solution; when the temperature of the aluminum chloride solution drops to 45-55°C, stop adding the tungsten carbide powder dispersion, and add sodium hydroxide solution to the aluminum chloride solution once, the single addition amount of sodium hydroxide solution accounting for 1-2% of the initial mass of the aluminum chloride solution; irradiate the aluminum chloride solution with ultraviolet light during the heating process of the aluminum chloride solution; S4, repeat step S3 until the mass ratio of the added tungsten carbide powder dispersion to the aluminum chloride solution reaches 1-1.25:1, continue stirring for 3-4 hours and then filter to obtain tungsten carbide loaded with aluminum hydroxide gel; S5. Put the tungsten carbide loaded with aluminum hydroxide gel into a sintering furnace and keep it at 500-600°C for 4-6 hours. After the heat preservation is completed, evacuate the sintering furnace to 1-3×10 -1 Pa, and then nitrogen is filled into the sintering furnace and the temperature of the sintering furnace is increased to 1600-1700°C, and the temperature is kept again for 10-12 hours. After the heat preservation is completed again, tungsten carbide / aluminum nitride composite particles are obtained.
5. A refractory and wear-resistant castable combined with ultrafine powder according to claim 4, characterized in that: In step S3, the mass concentration of the sodium hydroxide solution is 10-15%.
6. A refractory and wear-resistant castable combined with ultrafine powder according to claim 4, characterized in that: In step S3, the irradiation power of the ultraviolet light is 800-1200W, and the irradiation distance is 5-10cm.
7. The refractory and wear-resistant castable combined with ultrafine powder according to claim 4, characterized in that: In step S5, during the nitrogen filling process, the pressure increase rate of the sintering furnace is 0.2-0.4 MPa / h, and the temperature increase rate is 5-8°C / min.
8. A refractory and wear-resistant castable combined with ultrafine powder and a preparation method thereof, used for preparing a refractory and wear-resistant castable combined with ultrafine powder as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: 1) adding corundum powder, silicon powder, silicon carbide powder, bauxite clinker, zircon, and tungsten carbide / aluminum nitride composite particles into a mixer according to the weight portions, and stirring for 10 to 20 minutes to obtain a mixture; 2) Divide the binder into 2 to 4 equal parts, heat the mixture while stirring, and heat the mixture at a rate of 3 to 5°C / min. For every 8 to 10°C increase in the temperature of the mixture, add one part of the binder to the mixture until all the binder is added to the mixture. Stop heating and continue stirring for 5 to 10 minutes to obtain a castable.